Antioxidant Effects of E. alba: A Narrative Review - Keyur Dudhat; Anita Wanjari; Yogi Tajane; Shubham Khanke (Journal of Pharmacy and Bioallied Sciences)
Eclipta alba Linn, commonly known as Bhringaraja, exhibits significant antioxidant activity as demonstrated in various studies. Research has shown that E. alba contains bioactive components such as wedelolactone, dimethyl wedelolactone, flavonoids, and sterols, contributing to its antioxidant properties. Studies have evaluated the antioxidant activity of E. alba through assays like DPPH scavenging and reducing power assays, highlighting its effectiveness in scavenging free radicals and reducing oxidative stress. Additionally, the total phenolic and flavonoid contents in E. alba extracts have been linked to its potent antioxidant capabilities, further supporting its role as a natural antioxidant source. Overall, E. alba antioxidant potential makes it a promising candidate for further exploration in the development of pharmacologically active natural products with antioxidant properties.